The Influence Of Work Culture And Work Discipline On Employee Performance At The Ministry Of Religion, Karawang District - Rena Suci Kusmiati; Enjang Suherman; Flora Patricia Anggela (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
Performance given by employees not enough effective Because Still there is mistakes were made and still are low level Discipline shown by employees , especially _ as consequence from related factors _ with culture work and discipline work . Although Lots thing that can done employee something business For increase results performance is important for they For prioritize discipline work and compliance to standards that have set . Objective from study This is For test connection between culture work and discipline Work to performance employee at the district ministry of religion karawang . Researcher in study This use methodology quantitative and amount sample taken _ 63 employees of the Ministry of Religion of Karawang Regency . Study done with method survey , with analysis range scale and multiple linear regression data analysis were used for the descriptive test , respectively . Analysis statistics used For gather proof hypothesis that culture work and discipline Work own significant influence _ to productivity employee . With the R2 value is 0.663 and the magnitude effect of 0.627 ( or 62.7%), variable additions that don't researched is the rest of 0.373 ( or 37.3%).